Diversity and distribution of diatoms in Bagmati River, Kathmandu, Nepal - Rai, Shiva Kumar; Khadka, Sudip (Himalayan Biodiversity, 2018)
Diversity and distribution of diatoms in different seasons from different localities and habitats of Bagmati River, Kathmandu was studied. Samples were collected as epilithic forms using a toothbrush, epipelic forms using a dropper, and epiphytic forms by squeezing aquatic macrophytes and were preserved in FAA solution. The dominant diatom taxa of Bagmati river were Achnanthes crenulata, Gomphonema pseudoaugur, Nitzschia linearis, N. palea, Pinnularia cf divergens and Surirella linearis. Out of 48 taxa reported, maximum taxa (87.5%) were found at Mulkharka site whereas taxa were minimum (39.58%) at Pashupati-Guheshwori site. The sizes of diatom cell, from largest to smallest, also followed the same pattern as above. Ten diatom taxa were common in all three sites. Seasonal and habitat diversity of diatom studied in Mulkharka site showed that the maximum number of taxa was reported during summer (92.85%) and least during winter (23.8%), and maximum taxa were found as epilithic (85.71%) followed by epipelic (38.09%) and epiphytic (33.33%).